GEOGRAPHICAL INVESTIGATIONS IN THE MANAGEMENT OF THE SVALBARD ENVIRONMENT - Ziaja, Wiesław (Quaestiones Geographicae, 2019)
The paper concerns specific features of exploration, geographical recognition, exploitation of natural resources, and economy of the archipelago. Development of the Svalbard system of nature protection areas and its impact on the environment and human activity is shown. Both the natural environment and Norwegian national interests are perfectly protected in Svalbard. Classical physico-geographical research was lost in significance to biological investigations (or to environmental science in the aspect of biotic components). Research activity in the human geography of Svalbard has mostly declined.